Effectiveness of Dry Needling And Positional Release Technique On Myofascial Trigger Points Of Upper Trapezius In Mechanical Neck Pain - Rokri, Poonam; Kumar, Prabhat; Gupta, Nital (Journal of Neonatal Surgery, 2025)
The upper trapezius muscle is frequently associated with active myofascial trigger points in the cervical region, a highly prevalent condition characterized by pain, restricted range of motion, and functional impairment. Dry Needling and Positional Release Technique (PRT) are two commonly used therapies to alleviate these symptoms. However, there is a lack of high-quality randomized controlled trials directly comparing the effectiveness of these techniques in patients with mechanical neck pain (MNP). The aim of this study was to compare the effectiveness of PRT on pain intensity, active cervical range of motion, and neck-related disability in individuals with mechanical neck pain. A total of 90 participants aged between 18 and 55 years, meeting specific inclusion criteria, were recruited for this randomized controlled trial. Group A, Group B, and Group C all received Dry Needling. All interventions were administered once a day for three consecutive days. Pain intensity was measured using the Visual Analogue Scale (VAS), functional disability was assessed using the Neck Disability Index (NDI), and cervical range of motion was measured using a universal goniometer. Secondary outcomes included patient-reported global perception of change and any adverse effects experienced during the intervention. Assessments were conducted 72 hours and one week after the intervention. Cohen’s d was used to calculate effect sizes and to identify group-by-time interaction effects. Improvement in the Dry Needling group was more pronounced. There was a mean reduction in pain of 3.8 cm on the VAS, an improvement of 11.4 ± 5.2 in the NDI, and a decrease of 9.6 ± 3.1 points on the NDI after one week. The control group showed only minimal changes, while the PRT group demonstrated moderate improvement. The effect sizes ranged from moderate to large. No serious adverse events were reported in any group. The study concluded that Dry Needling is more effective than either PRT alone or conventional therapy in managing neck pain associated with upper trapezius myofascial trigger points. Clinical judgment can guide the choice of technique, with PRT serving as a suitable alternative where appropriate.